2014
DOI: 10.1016/j.jaac.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Modification Treatment Augmenting Effects on Cognitive Behavioral Therapy in Children With Anxiety: Randomized Controlled Trial

Abstract: Objective Attention bias modification treatment (ABMT) is a promising novel treatment for anxiety disorders, but clinical trials have focused largely on stand-alone formats among adults. This randomized controlled trial examined the augmenting effects of threat-based ABMT on cognitive behavioral therapy (CBT) in clinically anxious youth. Method Sixty-three treatment-seeking children with anxiety disorder were randomly assigned to 1 of the following 3 treatment groups: ABMT + CBT; ABMT placebo + CBT; and CBT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 27 publications
(45 reference statements)
8
97
2
2
Order By: Relevance
“…While this might minimize deleterious effects, it limits applicability to subsets of anxious children. Other studies that have not pre-selected on the basis of pre-treatment bias direction have found mixed results regarding bias modification and anxiety reductions (e.g., Bechor et al, 2014;Cowart & Ollendick, 2011;Rozenman et al, 2011;Shechner et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While this might minimize deleterious effects, it limits applicability to subsets of anxious children. Other studies that have not pre-selected on the basis of pre-treatment bias direction have found mixed results regarding bias modification and anxiety reductions (e.g., Bechor et al, 2014;Cowart & Ollendick, 2011;Rozenman et al, 2011;Shechner et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Por ejemplo, Boettcher, Hasselrot, Sund, Andersson y Carlbring (2014) han hallado que en el tratamiento de la ansiedad social, un procedimiento de MSC-A no añade ninguna mejoría a los participantes en un programa de terapia conductual están-dar a través de Internet. En otro caso, la combinación de TCC y MSC-A frente a la TCC combinada con relajación no arrojó resultados superiores en una muestra con fobia social (Shechner et al, 2014). Sin embargo, como se ha indicado previamente, la combinación de MSC-I con TCC sí ha mostrado ser superior al entrenamiento MSC-I aislado y a la no intervención en población con depresión (Williams et al, 2013).…”
Section: Discussionunclassified
“…We chose ABMT as a task for attentional retraining in the context of mental health because it has been studied extensively [32,37,87], has been deployed in the context of mobile digital interventions [88], has been successfully modified to include game-based elements, showing that its efficacy is resilient to modifications to its core format [88], and because of the ease of integrating customized stimuli -in our case, in the form of faces. While early work on ABMT (2010) highlighted it as a promising new treatment with medium to large effect sizes [32], a 2015 follow-up meta-analysis showed smaller effect sizes that fell below clinical relevance [89]; however, a 2017 meta-analysis [37] suggests that the discrepancy might be due to methodological differences in how the meta analyses were conducted.…”
Section: On the General Efficacy Of Attentional Retrainingmentioning
confidence: 99%
“…However, limitations of Internet-based CBT programs, such as the reading and language requirements, financial and time costs of localization, and the required time investment that is difficult for users to achieve suggest that other approaches might need to be deployed in tandem. Further, Computerized Cognitive Training (CCT), such as ABMT, has been applied adjacent [87] to Internetbased CBTs, showing potential in blending approaches.…”
Section: Blending and Extending Existing Therapeutic Approachesmentioning
confidence: 99%